Cell-type specific reductions in interneuron gene expression within the cingulate gyrus of schizophrenia and bipolar disorder subjects - David M. Krolewski; Huzefa Khalil; Maria Waselus; Marquis P. Vawter; Blynn G. Bunney; Richard M. Myers; Francis S. Y. Lee; Alan F. Schatzberg; William E. Bunney; Huda Akil; Stanley J. Watson (Schizophrenia)
Abstract Schizophrenia (SZ) and bipolar disorder (BP) patients share overlapping neurocognitive deficits of varied magnitude. Neuroimaging in patients and postmortem gene expression analyses suggest that compromised cingulate gyrus GABA-ergic interneurons may contribute to cognitive impairments in SZ and BP. To address this, we used radioactive in situ hybridization to investigate potential gene expression signatures for SZ and BP using interneuron cell-type specific markers including glutamic acid decarboxylase (GAD67), parvalbumin (PV), somatostatin (SST), and vasoactive intestinal peptide (VIP) within specific Brodmann’s areas (BA) of the cingulate gyrus. We report reduced GAD67 mRNA in anterior midcingulate cortex (aMCC) of BP subjects within BA24c’, the most dysregulated subregion across disorders that also demonstrated reduced PV and VIP mRNA in the SZ group. In the retrosplenial (RSC) and ectosplenial (ESC) cortices, decreases in PV expression were shared by both SZ and BP subjects. Our results show unique and shared transcription signatures of two disorders in specific cingulate gyrus regions and cell types. SZ and BP displayed divergent aMCC gene expression reductions suggesting transcriptional changes are associated with disease-specific gene/subregion signatures, potentially underlying differential subregional dysregulation within areas associated with error detection/action monitoring and the salience network. In RSC/ESC, transcriptional changes are associated with more common expression patterns, possibly related to overlapping effects on visuospatial memory processing and allocation of attentional resources involving the default mode network.